Optimized image processing and clustering to mitigate security threats in mobile ad hoc network - Ibrahim A. Alameri; Jawad Kadhim Mutar; Ameer N. Onaizah; Iftikhar Ahmed Koondhar (Universitas Ahmad Dahlan, 2020)
Since there are provisions of many attributes that are not possible or difficult to follow by networks conventionally, mobile ad-hoc networks are extensively deployed. This application starts through the defense sectors, the sensory node presents in the hostile territories down to the gadgets for congestion communication in traffic by general transportation when travelling for adequate provision of infrastructure during disaster recovery. As a lot of importance related to (mobile ad hoc network) MANET application, one important factor in ad-hoc networks is security. Using image processing for securing MANET is the area of focus of this research. Therefore, in this article, the security threats are assessed and representative proposals are summarized in ad-hoc network’s context. The study reviewed the current situation of the art for original to security provision called mobile ad hoc network for wireless networking. The threats to security are recognized while the present solution is observed. The study additionally summarized education erudite, talks on general issues and future instructions are recognized. Also, in this study, the forecast weighted clustering algorithm (FWCA) is employed as a cluster head over weighted clustering algorithm (WCA) is examined as quality in cluster-based routing, service is highly significant with MANET.